Oxidative Stress in Parkinson's Disease: A Systematic Review and Meta-Analysis - Wei, Zexu; Li, Xiaowan; Li, Xixi; Liu, Qingshan; Cheng, Yong (Frontiers in Molecular Neuroscience, 2018)
Oxidative stress has been suggested to play a key role in Parkinson's disease, but inconsistent results were found in clinical studies. This study sought to quantitatively summarize the blood and cerebrospinal fluid (CSF) oxidative stress marker data in PD patients. We performed a systematic search of PubMed and Web of Science, and studies were included if they provided data on peripheral blood and CSF oxidative stress marker concentrations in PD patients and healthy control (HC) subjects. Data were extracted by three independent investigators from 80 included studies encompassing 7,212 PD patients and 6,037 HC subjects. Of the 22 oxidative stress markers analyzed, random effects meta-analysis showed that blood concentrations of 8-OhdG, MDA, nitrite, and ferritin were increased in patients with PD compared with HC subjects. In contrast, we showed that blood levels of catalase, uric acid, glutathione, and total-cholesterol were significantly down-regulated in patients with PD when compared with controls. There were no significant differences between PD patients and HC subjects for blood, Mn, Cu, Zn, Fe, SOD, albumin, glutathione peroxidase, vitamin E, ceruloplasmin, triglycerides, lactoferrin, transferrin, LDL-cholesterol, and HDL-cholesterol. Due to the limited number of CSF studies with small sample size, this meta-analysis only showed non-significant association between CSF 8-OhdG and PD. The findings of our meta-analysis demonstrated higher blood concentrations of 8-OhdG, MDA, nitrite and ferritin, and lower blood concentrations of catalase, uric acid, glutathione and total-cholesterol in PD patients, strengthening the clinical evidence that PD is accompanied by increased oxidative stress.